2020
DOI: 10.1016/j.critrevonc.2020.103110
|View full text |Cite
|
Sign up to set email alerts
|

Self-expandable metal stent (SEMS) placement or emergency surgery as palliative treatment for obstructive colorectal cancer: A systematic review and meta-analysis

Abstract: Previous meta-analyses on palliative treatment of malignant colorectal obstruction with Self-Expandable Metal Stent (SEMS) or emergency surgery reported contradictory results for morbidity, and frequently included extracolonic obstruction. Therefore, the current meta-analysis aimed to exclusively analyze palliative treatment for primary obstructive colorectal cancer, with early complication rate as a primary outcome. A systematic literature search was performed on studies comparing palliative SEMS and emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Results showed that 30-day mortality was higher in those patients undergoing a surgical procedure (OR 0.4; 95% CI 0.28-0.69). 103 Early complications were more frequent in the surgical group, whereas late complications occurred more frequently after SEMS, mainly re-obstructions. Another meta-analysis in the same setting only including randomized controlled trials (four studies, 125 patients), showed no differences in 30-day mortality or mean survival between those patients undergoing SEMS or emergency surgery, with a shorter hospital stay in SEMS group.…”
Section: Palliative Surgery and Stentsmentioning
confidence: 86%
“…Results showed that 30-day mortality was higher in those patients undergoing a surgical procedure (OR 0.4; 95% CI 0.28-0.69). 103 Early complications were more frequent in the surgical group, whereas late complications occurred more frequently after SEMS, mainly re-obstructions. Another meta-analysis in the same setting only including randomized controlled trials (four studies, 125 patients), showed no differences in 30-day mortality or mean survival between those patients undergoing SEMS or emergency surgery, with a shorter hospital stay in SEMS group.…”
Section: Palliative Surgery and Stentsmentioning
confidence: 86%
“…Although the analysis showed that SEMS provided shorter operative and recovery time, and comparable complication and 30-day mortality rates, a higher clinical success rate was reported in the primary surgery group. A more recent systematic review and meta-analysis by Veld et al [ 22 ] included 18 studies with a sum of 1,518 subjects and exclusively focused on the early postoperative period. The authors concluded that SEMS was superior to primary surgery in the palliative setting mainly due to lower complication rates and faster recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of patients with large BO caused by colorectal cancer undergoing SEMS placement or emergency surgery with palliative intent, eighteen studies (randomized controlled trials and comparative observational studies) with 1518 patients were included. Results showed that 30-day mortality was higher in those patients undergoing a surgical procedure (OR 0.4; 95% CI 0.28-0.69) [103]. Early complications were more frequent in the surgical group, whereas late complications occurred more frequently after SEMS, mainly re-obstructions.…”
Section: Recommendation and Suggestionsmentioning
confidence: 96%